Efisiensi penggunaan input pada usahatani tomat belimbing di Kabupaten Muna - Iko, La Ode; Abdullah, Weka Gusmiarty; Fausayana, Ine; Iswandi, R. Marsuki; Rianse, Ilma Sarimustaqiyma (Universitas Halu Oleo, 2023)
This study aims to analyze the factors that affect the production of carambola tomato farming, and analyze the allocative efficiency of input use in carambola tomato farming in Muna Regency. The population in this study were all carambola tomato farmers in Kabawo District, Muna Regency. Sampling was carried out using a cluster random sampling technique. The number of samples in this study was 75 farmers. Data analysis used was multiple linear regression of the Cobb-Douglas production function model and allocative efficiency. The results showed that the factors that significantly influenced the production of carambola tomatoes were land area and fertilizer. While the factors that did not significantly influence the production of carambola tomatoes were seeds, herbicides, and labor. The use of land area inputs in carambola tomato farming in Muna Regency was not efficient, while the use of seed, herbicide, labor and fertilizer inputs was inefficient. Keywords: carambola tomato farming; Cobb-Douglas; production factors; efficiency